Coronary Microcirculation in Aortic Stenosis: A Physiological Hornets' Nest. (August 2019) - McConkey, Hannah Z.R.; Marber, Michael; Chiribiri, Amedeo; Pibarot, Philippe; Redwood, Simon R.; Prendergast, Bernard D.
Abstract : Aortic stenosis is a heterogeneous disorder. Variations in the pathological and physiological responses to pressure overload are incompletely understood and generate a range of flow and pressure gradient patterns, which ultimately cause varying microvascular effects. The impact of cardiac-coronary coupling depends on these pressure and flow effects. In this article, we explore important concepts concerning cardiac physiology and the coronary microcirculation in aortic stenosis and their impact on myocardial remodeling, aortic valve flow patterns, and clinical progression. Abstract : Supplemental Digital Content is available in the text.